Results and Performance of the World Bank Group 2022 : Concept Note - Independent Evaluation Group (Washington, DC : World Bank, 2022)
The Results and Performance of the World Bank Group (RAP) report 2022 presents an annual review of evidence from IEG evaluations and validation work on the development effectiveness of the World Bank Group. This year’s RAP will focus on the country level. The Bank Group’s outcome orientation agenda emphasizes high-level outcomes, and, by focusing on the country level, the 2022 RAP aligns with that agenda. This focus also responds to the interest of members of the Bank Group’s Board of Executive Directors for reporting on country level performance. In this context, the RAP will conduct an in-depth analysis of country level evidence contained in IEG’s Country Program Evaluations (CPEs) and Completion and Learning Report Reviews (CLR Reviews) through two types of analyses. First, overall country program performance will be assessed by tracking country program ratings over time. Second, the country program will be used as the entry point to examine the extent to which the Bank Group’s support (i.e., project portfolio and Advisory Services and Analytics) contributed to the achievement of the objectives of the Country Partnership Framework (CPF) and the intended development outcome. Furthermore, the extent to which there was a line of sight between the development outcome and high-level outcomes will also be examined.